A case of isolated sinus bradycardia as an unusual presentation of adrenal insufficiency. (September 2021) - Reyes, Jonathan Vincent M.; Majeed, Hafsa; Song, David; Ahmad, Saad; Bray, Ashley; Almas, Talal; Alshamlan, Abdulaziz; Lieber, Joseph J.
Abstract: Introduction: Sinus bradycardia is a common entity encountered in clinical practice. The differential diagnosis is quite broad; it can be an incidental finding in otherwise healthy adults or the first clue to a lethal pathology. Case presentation: This case highlights a patient who presented with symptomatic sinus bradycardia, which resulted in syncope requiring admission for permanent pacemaker implantation and later found to have an underlying adrenal insufficiency (AI). Patient's underlying hyponatremia was corrected but bradycardia persisted and after the initiation of steroids, bradycardia resolved. Therefore, the likely culprit for bradycardia was AI. Discussion: Multiple disease processes that manifest with sinus bradycardia are commonly due to the increased vagal tone or the presence of intrinsic conduction disorders. Sinus bradycardia is a common clinical finding with a broad differential including intrinsic and extrinsic causes of sinus node dysfunction or AV block. Conclusion: It is imperative for clinicians to be aware of rare etiologies for underlying symptomatic bradycardia. While extremely effective at preventing symptomatic bradycardia, avoiding a pacemaker by correcting the underlying etiology of symptomatic bradycardia may improve quality of life and avoid an unnecessary procedure. Highlights: Sinus bradycardia is a common entity encountered in clinical practice. Differential diagnosis is broad; as it can be an incidental finding in otherwise healthy adults or the first clue to a lethal pathology. Multiple disease processes manifest with sinus bradycardia commonly due to increased vagal tone (e.g: inferior wall myocardial infarction, drug or toxin exposures, infections, sleep apnea, hormonal and electrolyte disturbances, hypoglycemia, and increased intracranial pressures) or due to intrinsic conduction disorders (e.g sick sinus syndrome, sinus arrest, SA nodal blocks). Glucocorticoids have been suggested as having a direct inotropic effect as well as a permissive effect on cardiac myocytes in response to vasoactive peptides like epinephrine and angiotensin II that antagonize the sympathetic nervous system adrenergic receptors. It has been proposed that glucocorticoids upregulate expression of ion channels including IKs (mink, KvLQT1), and IKr (hERG, MiRP1) which induce outward potassium currents by inducing expression of serum- and glucocorticoid-inducible kinase (SGK1). Lack of glucocorticoids thereby extends the duration of action potential resulting in conduction abnormalities.